Cancer diagnosis, treatment and engagement with Psycho-oncology services- the patients' perspective - Carter, Eva (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2026)
The burden of cancer worldwide is rising, with 20 million new diagnoses annually and 9.7 million deaths. The psychological needs of cancer patients are increasingly recognised, and specialist psycho-oncology teams are developing. Despite this, various barriers diminish access to psycho-oncology services. This work aimed to better understand the experience of cancer patients and their families, and to assess their attitudes towards different aspects of the psycho-oncology service. This was a cross-sectional survey completed on the oncology day-ward of a large urban hospital in Ireland, using an established survey tool. Patient-rated distress at cancer diagnosis, treatment and attitudes towards psycho-oncology services were assessed in 142 cancer patients. This study found that women reported more extreme distress than men during cancer diagnosis and treatment. Patients were likely to perceive their families as more distressed than themselves, and report more extreme distress at diagnosis than treatment. Patients reported work, fatigue, and fear for the future as areas of life most extremely affected by cancer. Under one third of cancer patients (30.3%) knew the meaning of `psycho-oncology', and two thirds (67.2%) were ambivalent about a referral. One fifth (21.0%) would be somewhat/extremely uncomfortable disclosing attending palliative care, compared to 17.9% for psychiatry, 14.4% for psychology, and 5.8% for cardiology. More patients were happy to disclose taking medication for physical over psychological symptoms. On multi-variable testing, female gender was independently associated with higher patient distress at diagnosis and treatment and pre-existing psychiatric/psychological difficulty was independently associated with belief that a psycho-oncology referral would be beneficial. This study highlights high rates of extreme distress for cancer patients, particularly women, and their families and limited awareness of psycho-oncology services. This emphasises the need for enhanced, targeted, gender-aware, family-oriented psychological supports during cancer diagnosis and treatment.
APPROVED
Keywords: Mental illness; Oncology; Psychological distress; Psycho-oncology; Cancer; Distress; Mental health